Assessment of the sensitivity and specificity of serological (IFAT) and molecular (direct‐PCR) techniques for diagnosis of leishmaniasis in lagomorphs using a Bayesian approach. Issue 3 (15th June 2016) - de la Cruz, María Luisa; Pérez, Andres; Domínguez, Mercedes; Moreno, Inmaculada; García, Nerea; Martínez, Irene; Navarro, Alejandro; Domínguez, Lucas; Álvarez, Julio
Abstract: Leishmaniasis, caused by Leishmania infantum, is a vector‐borne zoonotic disease that is endemic to the Mediterranean basin. The potential of rabbits and hares to serve as competent reservoirs for the disease has recently been demonstrated, although assessment of the importance of their role on disease dynamics is hampered by the absence of quantitative knowledge on the accuracy of diagnostic techniques in these species. A Bayesian latent‐class model was used here to estimate the sensitivity and specificity of the Immuno‐fluorescence antibody test (IFAT) in serum and a Leishmania ‐nested PCR (Ln‐PCR) in skin for samples collected from 217 rabbits and 70 hares from two different populations in the region of Madrid, Spain. A two‐population model, assuming conditional independence between test results and incorporating prior information on the performance of the tests in other animal species obtained from the literature, was used. Two alternative cut‐off values were assumed for the interpretation of the IFAT results: 1/50 for conservative and 1/25 for sensitive interpretation. Results suggest that sensitivity and specificity of the IFAT were around 70–80%, whereas the Ln‐PCR was highly specific (96%) but had a limited sensitivity (28.9% applying the conservative interpretation and 21.3% with the sensitive one). Prevalence was higher in the rabbit population (50.5% and 72.6%, for the conservative and sensitive interpretation, respectively) than in hares (6.7% and 13.2%). Our results demonstrate that the IFAT may be a useful screening tool for diagnosis of leishmaniasis in rabbits and hares. These results will help to design and implement surveillance programmes in wild species, with the ultimate objective of early detecting and preventing incursions of the disease into domestic and human populations. Abstract : Lagomorphs have been identified as new potential reservoirs for leishmaniasis, but there is currently little knowledge about the epidemiology of the disease in these species. Here, we evaluate the usefulness of immunofluorescence antibody test and direct‐PCR in two populations of rabbits and hares, and demonstrate that prevalence of infection was important in rabbits, and that IFAT may be a useful screening test for diagnosis of leishmaniasis in lagomorphs.